The effects of wound dressings on the dose at surface and depth of maximum dose (dmax) for photon and electron beam radiotherapy - Raizulnasuha Binti Ab Rashid; Norhayati Dollah; Reduan Abdullah; Wan Nordiana W. Abd Rahman (Journal of Medical Physics and Biophysics, 2017)
The presence of wound dressing at the patients’ skin surface during radiotherapy treatment may potentially alter the dose at surface and shift the dose distribution at depth. In this study, the effects of different types of wound dressing to the radiotherapy treatment were investigated. The dose measurement at surface and dmax were done using different energy of photon and electron beams at 100 cm source to surface distance (SSD). Markus parallel plate ionization chamber and solid water phantom were used to quantify the dose with the dressing types used are Alderm +Plus, Actisorb Plus 25, Gauze and Duoderm CGF Extra Thin. The results show increment of surface dose up to 93.9% by wet gauze for photon beams and around 21% of dose increase for electron beams. Effects of dressing to the the dose at dmax indicate shift of dose distribution towards surface with reduction of dose around 10 % in wet condition for photon beam and up to 35 % for electron beams. Significant changes in surface dose and dose at dmax due to the wound dressing indicate the presence of wound dressing during radiotherapy need to taken in account in calculating dose to the target.